Cultural Properties of Cryopreserved Thymic Multipotent Stromal Cells and Fetal Skin and Muscle-Derived Cells - Nikolska, Valentina; Semenova , Yanina-Maria; Taranukha, Lyuba; Nikolsky, Ihor (Problems of Cryobiology and Cryomedicine, 2021)
The paper provides a comparison of properties of cryopreserved fetal murine multipotent stromal cells (MSCs) of skin-muscular origin and those derived from adult thymus in culture in vitro. Fetal MSCs showed a 30% higher number of average population doublings within 24 hrs, and 41% lower average population doubling time. It was found that the fetal MSCs of the 4th passage had a 39% higher clonogenic activity than the adult thymus-derived ones. Fetal MSCs and those derived from adult thymus differentiated in osteogenic and adipogenic lineages with equal efficiency in special culture media. Fetal and thymus-derived MSCs were characterized by almost the same high ability of contact interaction with thymocytes, and the fibroblast-lymphocyte rosette (FLR) formation. They were far less active in FLR formation with lymph node cells. This indicated the presence of membrane affinity for immature lymphoid cells in both MSC subpopulations. The results showed the fetal MSCs to be significantly different from the adult thymus-derived MSCs by more active kinetics of growth and clonogenic potential. However, both cell subpopulations had virtually the same ability for linear differentiation and showed high activity during contact with immature lymphoid cells. Linear differentiation and the ability to interact with lymphocytes were found to be quite stable properties of MSCs, but a proliferative activity and in vitro colony formation distinguished significantly in different types of MSCs. This can be taken into account when choosing the cells for therapy, research and results assessment. Probl Cryobiol Cryomed 2021; 31(3): 249–257